2016
DOI: 10.1111/1756-185x.12917
|View full text |Cite
|
Sign up to set email alerts
|

Passive anterior tibial translation in women with and without joint hypermobility: an exploratory study

Abstract: HM women showed significantly higher TT distances, which were even more accentuated in those having symptoms. The findings point toward less passive stability of the knee joint and thus maybe a need of higher muscle activation in order to stabilize the joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…In recent years, generalized joint laxity (GJL) also has been shown to be a risk factor for ACL injury. 13,21,28 Stettler et al 27 reported higher values for AKL in individuals with higher GJL scores compared with those with normal mobility. In addition, GJL scores are higher in women than in men 10 ; this difference between men and women has been attributed to differences in sex hormone levels.…”
mentioning
confidence: 99%
“…In recent years, generalized joint laxity (GJL) also has been shown to be a risk factor for ACL injury. 13,21,28 Stettler et al 27 reported higher values for AKL in individuals with higher GJL scores compared with those with normal mobility. In addition, GJL scores are higher in women than in men 10 ; this difference between men and women has been attributed to differences in sex hormone levels.…”
mentioning
confidence: 99%
“…Regarding the relationship between the menstrual cycle and tissue structure of the ACL, it has been reported that estrogen receptors are present in the human ACL [5], and in vivo studies have reported that AKL increases during ovulation [8] and luteal phases [9]. Higher values for AKL in individuals with higher GJL scores compared to those with normal mobility have also been reported [16]. Previous studies have investigated the correlation between female hormones and plantar fascia elasticity, and reported that plantar fascia elasticity increases during ovulation, synchronous with high estrogen levels [10].…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, generalized joint laxity (GJL) has also been shown to be a risk factor for ACL injury [15]. Stettler et al [16] reported higher values for AKL in individuals with higher GJL scores compared to those with normal mobility. In addition, GJL scores are higher in women than in men [17]; this difference between men and women has been attributed to differences in sex hormone levels.…”
Section: Introductionmentioning
confidence: 99%
“…All investigators who completed the measurements were blinded to group allocation. The main results of the project were published elsewhere [19,[24][25][26]. The study was approved by Canton Bern's Ethics Committee (#229/2008) and all participants gave written informed consent.…”
Section: Methodsmentioning
confidence: 99%